The Role of Organizational Culture in Mediating The Influence of Budget Planning And Internal Control On Budget Performance At The Regional Office of The Directorate General of Treasury, South Sulawesi Province - Muh Akob; Edy Jumady; Saiful (Jurnal Pallangga Praja (JPP), 2026)
This study aims to analyze the influence of budget planning on budget performance and organizational culture, the influence of internal control on budget performance, the influence of organizational culture on budget performance, as well as the role of organizational culture in mediating the effect of budget planning and internal control on budget performance at the Regional Office of the Directorate General of Treasury in South Sulawesi Province. The background of this study is based on the importance of effective budget planning and internal control in supporting the achievement of optimal budget performance, while taking into account the role of organizational culture as a determinant of the successful implementation of policies. This research employs a quantitative approach using the Structural Equation Modeling-Partial Least Squares (SEM-PLS) method. The research sample consists of 57 employees, including structural officials, functional officials, and staff members. Data were collected through questionnaires designed based on the indicators of each variable, then analyzed to test validity, reliability, and the relationships among variables in the model. The results indicate that budget planning has a positive but insignificant effect on budget performance, while internal control has a significant effect on budget performance. In addition, organizational culture significantly influences budget performance and mediates the effect of budget planning and internal control on budget performance. Thus, it can be concluded that enhancing the quality of organizational culture strengthens the effectiveness of budget planning and internal control, thereby contributing to the achievement of better budget performance.